Endothelin-1 in systemic sclerosis - Mehrdad Aghaei; Farhad Gharibdost; Habib Zayeni; Maryam Akhlaghi; Sima Sedighi; Abduo Rahman Rostamian; Naser Aghdami; Mahdieh Shojaa (Wolters Kluwer Medknow Publications, 2012)
Introduction: Scleroderma is a systemic disorder with unknown etiology most notably characterized by skin thickening and organ damage. Endothelin-1 (ET-1) plays a role in skin fibrosis. The aim of this study was survey and comparison of ET-1 level in Systemic Sclerosis (SSc) patients with and without digital ulcer. Material and Methods: A cross-sectional analytical study conducted among the 95 patients with scleroderma in 2006 who were referred to the Rheumatology clinic in Shariati hospital of Tehran. The questionnaire was completed for every patient. Plasma level of endothelin-1 was also measured in all of them. The data was analyzed using SPSS software and statistical tests. Results: The result indicated, relationship among digital ulcers and digital pitting scars with plasma level of ET-1 were significant (P value < 0.05). We could not find any significant relationship between age and plasma level of ET-1. Conclusion: These data indicate plasma level of ET-1 in scleroderma patients with digital ulcer was higher than patients without digital ulcer. Thus, increase in plasma level of ET-1 could be effective in vascular damage, fibrosis, and skin thickness.